2012
DOI: 10.1186/1479-5876-10-133
|View full text |Cite
|
Sign up to set email alerts
|

Adipose derived mesenchymal stem cells transplantation via portal vein improves microcirculation and ameliorates liver fibrosis induced by CCl4 in rats

Abstract: IntroductionAdipose derived mesenchymal stem cells (ADMSCs), carrying the similar characteristics to bone marrow mesenchymal stem cells, only much more abundant and easier to obtain, may be a promising treatment for liver fibrosis. We aim to investigate the therapeutic potential of ADMSCs transplantation in liver fibrosis caused by carbon tetrachloride (CCl4) in rats as well as its underlying mechanism, and to further explore the appropriate infusion pathway.MethodsADMSCs were isolated, cultured and identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 48 publications
5
58
0
3
Order By: Relevance
“…ADRCs have been reported to inhibit fibrosis of the liver [15], but there has been no previous report of fibrosis being caused by the grafting of large numbers of these cells. This study demonstrates that the concentration of transplanted ADRCs affects the engraftment and quality of the grafted fat.…”
Section: Discussionmentioning
confidence: 99%
“…ADRCs have been reported to inhibit fibrosis of the liver [15], but there has been no previous report of fibrosis being caused by the grafting of large numbers of these cells. This study demonstrates that the concentration of transplanted ADRCs affects the engraftment and quality of the grafted fat.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) reside in various tissues, such as bone marrow, umbilical cord blood, placenta, liver, adipose tissue and others. MSCs undergo self-renewal but can differentiate into multiple cell lineages; and have demonstrated immunomodulation, inflammation suppression and antifibrogenic effects [15]. MSCs isolated from adipose tissue are called adipose derived stromal cells (ADSCs).…”
Section: Introductionmentioning
confidence: 99%
“…ADSCs exhibit plasticity, cell surface markers, and a differentiation capacity similar to bone marrow-derived MSCs (Bonora-Centelles et al 2009;Baer 2011;Harn et al 2012). According to previous reports, ADSCs not only differentiate into hepatocyte-like cells (Al Battah et al 2011;Abbas Sahebghadam 2012;Wang et al 2012) but can also restore liver function in animal models (Mohsin et al 2011;Harn et al 2012;Saito et al 2014). Several preclinical studies have shown the efficiency of ADSCs in the treatment of liver disease (Wang et al 2012;Koellensperger et al 2013).…”
Section: Introductionmentioning
confidence: 90%